QSPM budgeting development level analysis in Bank CenterCredit JSC - Nurgaliyeva, A.M.; Mynbayeva, D.Y.; Lambekova, A.N. (BUKETOV BUSINESS REVIEW, 2021)
Object: The purpose of this study is to identify the main problems of budgeting in second-tier banks in Kazakhstan based on the analysis of the development of the level of budgeting and modern methods of budgeting in Kazakh banks. Methods: The collected data for the assessment and development of budgeting were analyzed using the matrix method for evaluating internal (IFE) and external factors (EFE), and QSPM (Quantitative Strategic Planning Method). Findings: As a result of the QSPM analysis, the Bank can become aware of its position in the market and step up its activities to improve management accounting, including budgeting in the bank. Conclusions: QSPM analysis in JSC Bank CenterCredit revealed the main strengths and weaknesses of budgeting development, as well as existing opportunities and threats. As a result, it was revealed that the bank is aware of its position in the market and is stepping up its activities to improve management accounting, including budgeting in the bank.